The effect of educational videos through the tiktok application on increasing knowledge about caries of State Islamic High School: Study experimental - Pitri, Sulpia; Taursia Wisnu, Fredy Rendra; Yandi, Satria (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRAKIntroduction: Dental caries is a common oral health problem among teenagers, partly caused by low levels of knowledge about dental care. Social media can be an effective alternative for obtaining information and supporting learning activities, and one such platform is Tiktok. Objective the aim of this study was to analyze changes in knowledge regarding dental caries before and after providing educational video interventions through the TikTok application. Methods: This quantitative study used a quasi-experimental design. The population in this study consisted of 80 tenth-grade students at MAN 3 Padang City, selected using simple random sampling. Results: The results showed that before the intervention, most students had a moderate level of knowledge (49 students, 61.3%), while after viewing the educational videos, most students demonstrated good knowledge (54 students, 67.5%). There was a significant increase in knowledge levels before and after the educational video educational video intervention delivered via TikTok regarding dental caries among tenth-grade students at MAN 3 Padang City (p=0.004). Conclusion:  Knowledge about dental caries increased after the educational video intervention through the TikTok application. This research may serve as a reference for educators and healthcare professionals to utilize social media as an innovative and effective educational tool.KEYWORDS: tiktok, health education, educational videos, caries knowledge, teenagers Peningkatan pengetahuan mengenai karies setelah pemberian intervensi video edukasi melalui aplikasi tikTok pada siswa madrasah aliyah negeri: studi eksperimentalABSTRACTPendahuluan: Karies gigi merupakan masalah kesehatan gigi dan mulut yang sering terjadi pada remaja, salah satunya disebabkan oleh rendahnya pengetahuan tentang perawatan kesehatan gigi. Media sosial dapat menjadi alternatif yang efektif untuk mendapat informasi dan menunjang kegiatan pembelajaran, salah satunya adalah Tiktok. Tujuan penelitian ini adalah untuk menganalisis perbedaan pengetahuan mengenai karies gigi sesudah pemberian intervensi video edukasi melalui aplikasi TikTok Metode: Jenis penelitian ini adalah kuantitatif dengan desain kuasi eksperimen. Populasi dalam penelitian ini adalah seluruh siswa-siswi kelas X di MAN 3 Kota Padang sebanyak 80 yang diambil secara simple random sampling. Analisis data menggunakan uji wilcoxon. Hasil: Tingkat pengetahuan siswa sebelum diberikan video edukasi paling banyak dengan kriteria cukup yaitu 49 orang (61,3%), sedangkan tingkat pengetahuan siswa sesudah diberikan video edukasi paling banyak dengan kriteria baik yaitu 54 orang (67,5%) dan terdapat peningkatan tingkat pengetahuan sebelum dan sesudah diberikan video edukasi melalui tiktok mengenai karies gigi pada siswa kelas X MAN 3 Kota Padang (p=0,004). Simpulan: Terdapat peningkatan pengetahuan mengenai karies gigi setelah diberikan intervensi pemberian video edukasi melalui aplikasi TikTok. Penelitian ini diharapkan dapat menjadi referensi bagi tenaga pendidik dan tenaga kesehatan dalam memanfaatkan media sosial sebagai sarana edukasi yang inovatif dan efektif.KATA KUNCI: tiktok, edukasi kesehatan, video edukasi, pengetahuan karies, remaja